Economic, social and environmental benefits of eco-tourism to exploitation of natural resources of the soil and subsoil in Colombia (2015)
Latin American countries some decades have faced a greater acquisition search economic resources to make their economies grow and so give greater benefits to people i.e. improve the quality of life, remove the country from the poverty and in turn is popularized the exploitation of the subsoil resources taking into account that their economies was of primary nature i.e. farm and without changes that increase its value What are relied on the exploitation of coal, oil, gold and other natural resources of the subsoil this as an economical solution to an economic and social situation adversely but this solution generated a very large and problems with dimensions of environmental impact which still have not been understood and not even been measured quantitatively and qualitatively the consequences of this decision but as some scholars argued with the free trade agreement with North America failure to do so is bad and not doing so is worse in this case could think the same exploit them can bring displacement hunger and death and not to exploit them brings poverty and backwardness in terms of even neighboring countries not only with the so-called powers of the world countries. This so tragic and disheartening view allows us to see that we must find solutions that bring money into the coffers of the State and welfare to the inhabitants of these areas where there is water and crops and today there are only dust, the alternative that raises this writing is a concept is not new but which has not echoed on the rulers and leaders who have not opted for the and is sustainable development and to be more specific eco-tourism, taking advantage of the beauty of the landscapes of our Colombia and cordiality of our people who look that you amara more than foreign compatriots by the well who feel so much so there that deporting them by not doing things right and not having their papers in order and become force.